Bridging the Divide between Manual Gating and Bioinformatics with the Bioconductor Package flowFlowJo. (4th October 2009) - Gosink, John J.; Means, Gary D.; Rees, William A.; Su, Cheng; Rand, Hugh A.
Abstract : In flow cytometry, different cell types are usually selected or "gated" by a series of 1- or 2-dimensional geometric subsets of the measurements made on each cell. This is easily accomplished in commercial flow cytometry packages but it is difficult to work computationally with the results of this process. The ability to retrieve the results and work with both them and the raw data is critical; our experience points to the importance of bioinformatics tools that will allow us to examine gating robustness, combine manual and automated gating, and perform exploratory data analysis. To provide this capability, we have developed a Bioconductor package called flowFlowJo that can import gates defined by the commercial package FlowJo and work with them in a manner consistent with the other flow packages in Bioconductor. We present this package and illustrate some of the ways in which it can be used.